PENGARUH AMBULASI DINI TERHADAP WAKTU FLATUS PADA PASIEN POST SC DENGAN SPINAL ANASTESI DI RUANG NIFAS RSUD DR. R. SOEDJONO SELONG - Ilmi, Nurul (STIKES Mataram, 2019)
Sectio caesarea (SC) is an operative procedure performed under anesthesia so the fetus, placenta and amniotic born through an incision in the abdominal wall and uterus. Spinal anesthesia was chosen for the Sectio Caesarea relatively safe for the fetus. The problem that is often experienced by post Sectio Caesarea patients is distended abdomen due to accumulation of gas due to the decrease intestinal peristalsis. Early mobilization is nursing implementation that can be done to speed up the flatus time of patients that will reduce the accumulation of gas in the intestinal organs. The purpose of this study was to determine the effect of early mobilization against flatus time in post sectio caesarea patients with spinal anesthesia in RSUD DR.R. Soedjono Selong. This study uses a pre-experimental design using one-shot case study with purposive sampling technique. The number of respondents are 27 patients. The collection of data through documentation and observation by filling checklist time of flatus. The data obtained were analyzed by One Sample T Test with a significance level of 0.05. From the results, 25 people (92.6%) flatus in less than 24 hours and 2 people (7.4%) flatus between 24 to 48 hours and no respondents who flatus in more than 48 hours (0%) , and one sample test results obtained Test p value = 0.161 (> 0.05). It can be concluded that Ha accepted which means early ambulation influence on the flatus time in patients with postoperative Sectio Caesaria in post partum room of RSUD Dr. R. Soedjono Selong. Early ambulation can accelerate the return of gastrointestinal function and time flatus. Therefore it was important to early ambulation in patients with spinal anesthesia post Sectio Caesaria to prevent the occurrence of abdominal distension.